Pengaruh Media Audio Visual terhadap Peningkatan Pengetahuan Seputar HIV / AIDS - Wahyuni, Sri (Pro Health Jurnal Ilmiah Kesehatan, 2024)
According to data from the Executive Report on the Development of HIV AIDS and Sexually Transmitted Infectious Diseases (PIMS) for the first quarter of 2022, Central Java Province is in 3rd place in the five provinces with the highest number of AIDS, namely 14,617 cases. There is no cure for HIV/AIDS infection, resulting in an increase in HIV/AIDS cases every year which will have an impact on increasing morbidity and mortality rates, as well as having an impact on psychological and social problems. Therefore, promotive and preventive efforts are needed to introduce the wider community, especially the adolescent age group, about the dangers, prevention and control of HIV AIDS. One way to deliver education and health promotion about HIV AIDS is by using audio-visual media. This research aims to determine the effectiveness of using audiovisual media in increasing knowledge about HIV/AIDS. The type of research used is quantitative research with a Quasi Experimental research design using a Google form Pre-test and Post-test questionnaire with a Control Group Design approach. The research results showed that the age characteristics of the majority of respondents were less than 20 years old with a total of 250 people and the majority were female, 252 people. The average knowledge of students before and after being given health promotion through audiovisual media about HIV/AIDS in the experimental group showed p value (0.000) < α (0.05), meaning that there was a significant difference between the average knowledge of students before and after being given health promotion through audiovisual media about HIV/AIDS. Meanwhile, the control group showed p value (0.897) > α (0.05), meaning there was no significant difference between the average knowledge of students regarding HIV/AIDS. So it can be concluded that providing health promotion about HIV/AIDS through audiovisual media is effective in increasing students' knowledge about HIV/AIDS.   ABSTRAK                 Menurut data Laporan Eksekutif Perkembangan HIV AIDS dan Penyakit Infeksi Menurlar Seksual (PIMS) Triwulan I Tahun 2022, Provinsi Jawa Tengah berada pada urutan ke-3 Lima Provinsi dengan jumlah AIDS terbanyak, yaitu sebanyak 14.617 kasus. Belum adanya obat untuk infeksi HIV/AIDS, mengakibatkan peningkatan kasus HIV/ AIDS setiap tahun akan berdampak terhadap terjadinya peningkatan angka kesakitan dan kematian, serta mempunyai dampak pada masalah psikologi dan sosial. Oleh sebab itu, dibutuhkan upaya promotif dan preventif untuk memperkenalkan kepada masyarakat luas, khususnya pada kelompok usia remaja tentang bahaya, pencegahan, dan penanggulangan penyakit HIV AIDS. Salah satu cara penyampaian edukasi dan promosi kesehatan seputar HIV AIDS adalah dengan cara menggunakan media audio visual. Penelitian ini bertujuan untuk mengetahui efektifitas penggunaan media audiovisual dalam meningkatkan pengetahuan seputar HIV/AIDS. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan desain penelitian adalah Quasi Eksperimental menggunakan kuesioner google form Pre-test dan Post-test dengan dengan pendekatan Control Group Design. Hasil penelitian menunjukkan bahwa karakteristik usia responden mayoritas berada pada usia kurang dari 20 taun dengan jumlah 250 orang dan mayoritas berjenis kelamin perempuan sebanyak 252 orang. Rata-rata pengetahuan mahasiswa/i sebelum dan sesudah diberikan promosi kesehatan melalui media audiovisual tentang HIV/AIDS pada kelompok eksperimen menunjukkan p value (0,000) < α (0,05), artinya ada perbedaan yang signifikan antara rerata pengetahuan mahasiswa/i sebelum dan sesudah diberikan promosi kesehatan melalui media audiovisual tentang HIV/AIDS. Sementara pada kelompok kontrol menunjukkan p value (0,897) > α (0,05), artinya tidak ada perbedan yang signifikan antara rerata pengetahuan mahasiswa/i mengenai HIV/AIDS. Sehingga dapat disimpulkan bahwa pemberian promosi kesehatan tentang HIV